Identificação do grau de aceitação dos irrigantes do perímetro do Betume-SE, quanto à qualidade da água de drenagem em reuso direto - Santos, Heraldo Bispo dos (2015)
Given the insufficient amount of water available to meet the demand of rice cultivation irrigation, the Associação dos Parceleiros do Distrito de Irrigação do Betume began to recirculate up to 100% of the system drainage water, most often without dilution. Despite the water reuse in irrigation be worldwide considered a best practice to save the resource, this practice should occur given the technical principles and parameters of existing norms, aiming the safety of direct and indirect users and the prospect of sustainability of agro-ecosystems. This research aimed to identify the degree of irrigator´s acceptance about the reuse of drainage water for irrigation of rice growing. In carrying out this study, secondary data were explored by consulting records, documents, and literature review. Primary data was obtained through systematic observation; semi-structured interviews with 88 local farmers; and measurement of physical, chemical and microbiological parameters of drainage water. Sources of pollution and contamination of anthropogenic origin were found. Three water quality parameters (BOD, turbidity and thermotolerant coliforms) were above the regulatory limits, indicating a need for monitoring and treatment of drainage water. 80 % of farmers accept the reuse of drainage water for irrigation that is taking place, but require adjustments of the current situation in order to minimize economic losses, risks to health and degradation of natural resources, ultimately contributing to the improvement of local sustainability.